AB0768 Osteomyelitis complicating digital ulcers in systemic sclerosis. (12th June 2018) - Chiapparoli, I.; Locatelli, F.; Orsolini, P.; Caporali, R.; Montecucco, C.; Codullo, V.
Abstract : Background: Skin ulcers are a frequent manifestation of systemic sclerosis (SSc). Skin ulcers are painful, represent a cause of disability and heavily affect patients' quality of life. The presence of local infection may be responsible for osteomyelitis (OM) of the underlying bone. If gangrene develops, surgical amputation may be required. At the moment is not clear if there are predisposing factors to osteomyelitis development. Objectives: To describe a population of SSc patients affected by cutaneous ulcers and osteomyelitis Methods: We collected data of SSc patients satisfying the 2013 ACR criteria for SSc referring to our outpatient clinic from January 1st 2016 to December 31st 2017. The patient's data were evaluated on the basis of individual clinical records, including demographic, clinical and serological findings. Cutaneous ulcers were defined as epithelial loss and loss of dermis; post-traumatic skin lesions were excluded. In cases suspected of infection, microbiological investigations were carried out. We have diagnosed OM by clinical, radiological and laboratory means, in particular the presence of pain, swelling, fever, erythema, purulent secretions, blood chemistry alterations and typical radiological characteristics at either plain X ray and/or MRI. Statistical analysis was performed using STATA software for descriptive analysis and groups comparisons. Given the low number of events only univariate analysis was conducted. Results: A total of 189 patients were enrolled in the study. Of them, 21 (11.1%) were males, mean age was 64.39±12.5 years and median disease duration 11.59 (5.6–19.3) years. A diffuse cutaneous (dcSSc) involvement was present in 50 (26.5%), limited cutaneous (lcSSc) in 131 (69.3%) and a limited disease in 8 patients (lSSC) (4.2%). Digital ulcers (DU) were present in 29 patients (15.3%) and in 5 cases (2.6%) were complicated by the occurrence of OM. The pathogens responsible of the infections were isolated in 3/5 (60%) cases and were represented by: Methicillin-sensitive Staphilococcus Aereus (2 cases) and P. Aeruginosa, also multisensitive. OM affected the third finger of right hand in 2 (40%) patients, the second finger of right hand in 1 (20%) patient and the third finger of left hand in 2 patients (40%). In 2 cases (40%) surgical amputation had to be performed. Patients with OM were significantly younger (54.9±16.07 vs 64.65±12.34, p 0.0432) and had higher CRP levels than the rest of the patients (1.27±0.59 vs 0.42±0.74, p 0.0061) In patients with DU, the only predictive factor for the development of OM was the total number of ulcers in the single patient (OR 2.27, 1.39–3.71, p<0.001) while no significant influence was found for other demographical or disease specific parameter. Conclusions: OM is a severe complication of DU in SSc. In most cases the aetiologic agents are community-acquired pathogens. SSc patients with OM were younger but did not show any other obvious distinguishing feature. The number of ulcers in the single patients were predictive of OM development. Further and larger studies are needed to address this aspect of the microvascular involvement of SSc. Disclosure of Interest: None declared